PERANCANGAN ULANG USER INTERFACE PADA APLIKASI JUST MEME MENGGUNAKAN METODE DESIGN THINKING - Gozalianto, Rafli Gozalianto; Himala Praptami Adys; Baizul Zaman (KHARISMA Tech, 2024)
This study aims to modify the user interface (UI) of the Just Meme application by applying the design thinking approach to achieve a better UI. Data collection was conducted by distributing questionnaires to 21 respondents using Google Form. The collected data was then processed using the System Usability Scale (SUS) method. The initial UI testing with the SUS method resulted in a score of "41.19" with a rating of "Okay." Based on these results, the Just Meme application was redesigned using the Design Thinking approach. The new prototype resulting from this method was then retested using the SUS method. The prototype testing yielded a score of "76.30" with a rating of "Excellent”. It can be concluded that through the design thinking approach in redesigning the UI, the study successfully addressed the issues faced by users and produced a design with improved usability.